Penerapan Model Pembelajaran Team Pair Solo (TPS) untuk Meningkatkan Hasil Belajar Siswa Kelas VII - Syahri Alqurni; Swasti Maharani; Sri Sunarni (Journal on Education, 2024)
This research aims to improve the mathematics learning outcomes of class VII students at SMP Negeri 11 Madiun by using the Team Pair Solo learning model. This type of research is Classroom Action Research (PTK). The data collection technique used in this research is a test. Data analysis in this research uses quantitative and qualitative analysis. This research consists of two cycles. At the pre-cycle stage, the learning outcomes of students who achieved the KKM score were 36.7% or 11 students. The results of this research show that in cycle I the students who achieved the KKM score or completed were 60% or 16 students and in the second cycle the students who achieved the KKM score were 83.3% or 25 students. Thus it can be concluded that the application of the Team Pair Solo learning model can improve student mathematics learning outcomes